2015
DOI: 10.1179/2042618615y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manual therapy with augmentative exercises for neck pain: a randomised clinical trial

Abstract: Objectives:To compare the effect of manual therapy (MT) and an augmentative exercise programme (AEP) versus MT and general neck range of motion (ROM) on functional outcomes for patients with neck pain. A secondary objective was to examine changes in self-report measures and quantitative sensory testing (QST) following MT and AEP. Methods: This was a randomised clinical trial. Seventy-two patients with neck pain were recruited. All patients received a single session of MT. Patients were randomly assigned to MT+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The present study was done on a subset of subjects from a larger RCT comparing two exercise programmes prescribed in conjunction with a single session of manual therapy, to determine if a specific augmentative exercise programme would better augment the effects of the manual therapy intervention than a non‐specific general neck ROM exercise. The primary study associated with the present trial found no difference in pain or disability outcomes between the two interventions (Petersen et al, ). The specific exercise was prescribed to augment the manual therapy intervention by targeting the same levels and facilitating motion in the same direction as the impairment.…”
Section: Methodsmentioning
confidence: 73%
See 3 more Smart Citations
“…The present study was done on a subset of subjects from a larger RCT comparing two exercise programmes prescribed in conjunction with a single session of manual therapy, to determine if a specific augmentative exercise programme would better augment the effects of the manual therapy intervention than a non‐specific general neck ROM exercise. The primary study associated with the present trial found no difference in pain or disability outcomes between the two interventions (Petersen et al, ). The specific exercise was prescribed to augment the manual therapy intervention by targeting the same levels and facilitating motion in the same direction as the impairment.…”
Section: Methodsmentioning
confidence: 73%
“…Previous studies examining ST muscle strength following manual therapy intervention showed improvements immediately after application of the technique but as no longer‐term follow‐up was done, the duration of these changes is unknown (Cleland et al, ; Liebler et al, ). The combination of manual therapy and exercise has previously been reported to effect change in self‐reported measures of pain and disability over 96 hours (Petersen et al, ). In the current study, we observed strength changes over a 96‐hour period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4. Reeducation of correct movement patterns within the spine, especially at the border of the cervical and thoracic segments (rotational movements), through targeted exercises of different degrees of complexity, and in the shoulder girdle [41][42][43][44][45][46][47].…”
Section: Physiotherapeutic Strategymentioning
confidence: 99%